2021
DOI: 10.1101/2021.04.06.438560
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A novel SNF2 ATPase complex inTrypanosoma bruceiwith a role in H2A.Z-mediated chromatin remodelling

Abstract: A cascade of histone acetylation events with subsequent incorporation of a histone H2A variant plays an essential part in transcription regulation in various model organisms. A key player in this cascade is the chromatin remodelling complex SWR1, which replaces the canonical histone H2A with its variant H2A.Z. Transcriptional regulation of polycistronic transcription units in the unicellular parasite Trypanosoma brucei has been shown to be highly dependent on acetylation of H2A.Z, which is mediated by the hist… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 101 publications
0
6
0
Order By: Relevance
“…Counterparts of yeast SWR1 H2A-to-H2A.Z exchange complex and NuA4 HAT complex components were identified, some of which were enriched where H2A.Z is prevalent at TSRs. A recent report indicates that both TbSWR1 and TbNuA4 complexes are indeed involved in the deposition of T. brucei H2A.Z (Vellmer et al 2021).…”
Section: Discussionmentioning
confidence: 98%
“…Counterparts of yeast SWR1 H2A-to-H2A.Z exchange complex and NuA4 HAT complex components were identified, some of which were enriched where H2A.Z is prevalent at TSRs. A recent report indicates that both TbSWR1 and TbNuA4 complexes are indeed involved in the deposition of T. brucei H2A.Z (Vellmer et al 2021).…”
Section: Discussionmentioning
confidence: 98%
“…Two YEATS domain-containing proteins have been identified in Tryp . brucei , TbYEA1 (also named TbSWRC1 in [ 53 ]) and TbYEA2 that appear to be involved in chromatin remodeling. TbYEA1, revealed to be a Gas41/Yaf9 homolog by structural analysis [ 53 ], is associated with the methyl-lysine reader protein TbZCW1 and the bromodomain protein TbBDF2 [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…brucei , TbYEA1 (also named TbSWRC1 in [ 53 ]) and TbYEA2 that appear to be involved in chromatin remodeling. TbYEA1, revealed to be a Gas41/Yaf9 homolog by structural analysis [ 53 ], is associated with the methyl-lysine reader protein TbZCW1 and the bromodomain protein TbBDF2 [ 34 ]. Further co-immunoprecipitation (co-IP) experiments showed that TbYEA1 interacts with TbRuvB2, a helicase protein that is conserved in the SWR1 chromatin remodeling complex [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations